OPTIMALISASI POTENSI ZAKAT MELALUI TINGKAT KESADARAN MASYARAKAT DALAM MENYALURKAN ZAKAT MAAL DIKELURAHAN TANJUNG JOHOR KECAMATAN PELAYANGAN - Rizandi; H Sissah; M. Maulana Hamza (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study aims to provide analysis and provide input to the zakat collection unit. The zakat collection unit orabbreviated UPZ is an organization formed by BAZNAZ to collect zakat in the management of agricultural tanjong johor village, serving district, jambi city during the activity zakat, devoted to distributing agricultural zakat in the community and realizing the importance of paying agricultural zakat when it is nishab and haul through institution that have been provided by BAZNAZ. The research used is descriptive qualitative. Descriptive qualitative research is a method in the form of research using a case study method or approach. The results of the study show that implementation of zakat on tanjong johor village, serving district, jambi city, the knowledge of the agricultural products in farmers related to the mahdhah worship which is reflected in the which has stipulations in its implementation, namely how and pillars of islam in practice is still minimal. Its application of issuing zakat, the majority of farmers in this sub-district only issue zakat on rice plants and very rarely issue zakat on other crops even though there are only some people who carry it out.